Performing emotions in early Europe - Maddern, Philippa C.; McEwan, Joanne; Scott, Anne M. (Brepols, 2018)
Drawing on a range of interdisciplinary approaches and innovative methodologies, this collection contributes ground-breaking new scholarship in the burgeoning field of emotions studies by examining how medieval and early modern Europeans communicated and 'performed' their emotions. Rejecting the notion that emotions are 'essential' or 'natural', this volume seeks to pay particular attention to cultural understandings of emotion by examining how they were expressed and conveyed in a wide range of historical situations. The contributors investigate the performance and reception of pre-modern emotions in a variety of contexts - in literature, art, and music, as well as through various social and religious performances - and in a variety of time periods ranging from the twelfth to the eighteenth centuries. These studies provide both case-studies of particular emotions and emotional negotiations, and examinations of how their categorisation, interpretation, and meaning has changed over time
Keywords: Geschichte 1500-1800; Gefühl; Affekt -- Motiv; Malerei; Europa; Konferenzschrift -- 2011 -- Perth; Aufsatzsammlung